2013
DOI: 10.1103/physrevd.88.045015
|View full text |Cite
|
Sign up to set email alerts
|

Oscillons and oscillating kinks in the Abelian-Higgs model

Abstract: We study the classical dynamics of the Abelian Higgs model employing an asymptotic multiscale expansion method, which uses the ratio of the Higgs to the gauge field amplitudes as a small parameter. We derive an effective nonlinear Schrödinger equation for the gauge field, and a linear equation for the scalar field containing the gauge field as a nonlinear source. This equation is used to predict the existence of oscillons and oscillating kinks for certain regimes of the ratio of the Higgs to the gauge field ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 48 publications
2
54
1
5
Order By: Relevance
“…Oscillons can be produced during preheating after different models of inflation [7][8][9][10][11], as well as in various types of field theories [12][13][14][15][16][17][18][19]. In [20], it has been shown that they form when a scalar field oscillates in a potential that opens up away from the minimum, i.e.…”
mentioning
confidence: 99%
“…Oscillons can be produced during preheating after different models of inflation [7][8][9][10][11], as well as in various types of field theories [12][13][14][15][16][17][18][19]. In [20], it has been shown that they form when a scalar field oscillates in a potential that opens up away from the minimum, i.e.…”
mentioning
confidence: 99%
“…Indeed, much recent work has been devoted to answering this question in a variety of inflationary models. If we focus only on real scalar field models, the dominant coherent configurations are oscillons [15][16][17]: long-lived, time-dependent localized configurations which have been shown to exist in many models of interest in cosmology and high-energy physics, from Abelian Higgs models [18,19] to the Standard Model (for particular parameter values) [20][21][22]. Within inflation, inflaton "hot spots" were reported in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison a typical solution of an asymmetric oscillon of Ref. [28] is also shown in Fig. 2 [dotted (green) lines] for the same value of q.…”
Section: Modulation Instabilitymentioning
confidence: 99%
“…Firstly it may reveal important features of superconductivity [33,34] allowing at the same time for analytical treatment. In fact the search for one dimensional solutions of the effective theory of superconductivity [35], namely the Gorkov-Eliashberg-Landau-Ginzburg approach, can be directly associated with the investigation of classical solutions of the (1+1)-dimensional Abelian-Higgs model [28]. Additionally, in most recent studies this model plays an important role in one dimensional holographic superconductors [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation